Análisis de cobertura en acueducto y estado del recurso hídrico en el departamento de La Guajira: Recopilación bibliográfica. (2025)
The degree project is focused directly on the verification of aqueduct coverage and, however, also on the quality of the IRCA in the department of La Guajira with the objective of determining the real situation regarding the supply, quality and consumption of the water resource that It is of vital importance for the development of any community. To analyze the objective, we collect information from government entities such as the IDEAM (Institute of Hydrology, Meteorology and Environmental Studies of Colombia), the ENA (National Water Study) and the Superintendency of Home Public Services, which are in charge of surveillance. , control and management of viable water supply sources for human consumption in the municipalities of La Guajira